Poverty as a Social Fact: Can It Be Eliminated or Only Reduced? - Sigdel, Bhim Raj (Journal of Productive Discourse, 2025)
Poverty eradication efforts have traditionally been framed within two dominant paradigms: individualistic and structural approaches. These perspectives often overlap internally yet diverge significantly in their definitions of poverty and proposed solutions. The individualistic school attributes poverty primarily to personal shortcomings, such as passivity, lack of motivation, or unwillingness to adapt, often focusing on behavioral reforms and empowerment strategies. In contrast, the structural school emphasizes broader socio-cultural, economic, and political factors, viewing poverty as the result of systemic inequalities, labor market failures, institutional discrimination, and historical marginalization. Although each perspective offers valuable insights, their contradictions suggest that neither framework alone sufficiently addresses the complexity and persistence of poverty across diverse contexts. This article proposes a synthesized model that integrates both individualistic and structural elements, arguing that a blended approach better compensates for the limitations inherent in each. By recognizing that individual agency operates within structural constraints, the proposed model seeks to create interventions that are both empowering at the personal level and transformative at the systemic level. Empirical analysis of urban contexts further demonstrates that while neither model alone successfully eradicates poverty, their combined application contributes meaningfully to its reduction. The study concludes by suggesting that future anti-poverty policies must adopt this integrated framework, emphasizing multidimensional strategies that are responsive to both personal and systemic dynamics.